s= - 3r/r-2
Use the second derivative to find out concavity
s' = (r-2)(-3) - (-3r)(1) / (r-2)^2
= 6 / (r - 2)^2
s" = (r-2)^2(0) - 6(2(r - 2) / (r - 2)^4
= -12 / (x - 2)^3
which is negative for x > 2 and positive for x < 2
the function is concave up in the interval (- infinity, 2)
and concave down in the interval (2, infinity)
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?